Performance of two Ips bark beetles and their associated pathogenic fungi on hosts reflects a species-specific association in the beetle-fungus complex - Shi, Xia; Fang, Jiaxing; Du, Huicong; Zhang, Sufang; Liu, Fu; Zhang, Zhen; Kong, Xiangbo (Frontiers in Plant Science, 2022)
When Ips bark beetles invade and colonize the host plants, their associated pathogenic fungal partners are carried into the phloem of the host trees. Host trees are lethally attacked by the beetle-fungus complex and the collective damage severely limits forestry production worldwide. It is of great importance to verify whether bark beetles and their associated fungi show concordant performance in terms of biology, physiology, and biochemistry on host trees. In this study, the two Ips bark beetles Ips typographus and Ips subelongatus (Coleoptera: Curculionidae, Scolytinae), their respective associated pathogenic fungi Endoconidiophora polonica and Endoconidiophora fujiensis, and their respective host plants Picea jezoensis and Larix olgensis were selected as test material. Cross-inoculation experiments were conducted indoors and outdoors to investigate the differences in reproduction and development of two beetles and infectivity of two fungi on two plants, as well as the differences in physiological responses of two plants to two fungal infections. The results showed that I. typographus and E. polonica had excellent host performance on P. jezoensis; however, neither successfully colonized and infected L. olgensis. In contrast, I. subelongatus and E. fujiensis showed strong host suitability on L. olgensis and some degree of suitability on P. jezoensis, although the host suitability of P. jezoensis for E. polonica was significantly higher than that for E. fujiensis. In addition, we found that the absolute amount of ergosterol accumulated on the lesion was positively correlated with lesion area. The ergosterol amount and lesion area were both strongly correlated with the release of host monoterpenes, but had no obvious correlation with the concentration of fungi-induced phenols on the lesion area and the side-chain oxidation of lignin in the xylem of the infected sites. Based on these results, we confirmed that “I. typographus-E. polonica” and “I. subelongatus-E. fujiensis” complexes both showed the most suitable consistent performances on their own traditional hosts, establishing a stable species-specific association relationship in these two beetle-fungus complexes, with the “I. subelongatus-E. fujiensis” complex showing broader host suitability. From the perspective of physiological responses of plants to fungal infections, monoterpenes are an important indicator of host suitability.